Ancillary Ligand Effects on Heteroleptic IrIII Dye in Dye‐Sensitized Photocatalytic CO2 Reduction: Photoaccumulation of Charges on Arylated Bipyridine Ligand and Its Control on Catalytic Performance. Issue 70 (13th November 2020) - Jo, Ju Hyoung; Choi, Sunghan; Cheong, Ha‐Yeon; Shin, Jae Yoon; Kim, Chul Hoon; Cho, Dae Won; Son, Ho‐Jin; Pac, Chyongjin; Kang, Sang Ook
Abstract: Herein, we report the synthesis, and photochemical and ‐physical properties, as well as the catalytic performance, of a series of heteroleptic Ir III photosensitizers (IrPSs), [Ir(C^N)2 (N^N Aryl )] +, possessing ancillary ligands that are varied with aryl‐substituents on bipyridyl unit [C^N=(2‐pyridyl)benzo[ b ]thiophen‐3‐yl (btp); N^N Aryl =4, 4′‐Y2 ‐bpy (Y=−Ph or −PhSi(Ph)3 ]. We found that the π ‐extension of bipyridyl ligand by aryl‐substitution put bipyridyl ligand in use as an electron relay unit that performed charge accumulation before delivering to the catalytic center, greatly improving the overall CO2 ‐to‐CO conversion activities. In a typical run, the aryl‐substituted IrPS ( t Bu IrP‐Ph Si )‐sensitized homogeneous systems (IrPS+Re I catalyst) gave a turnover number of 1340 ( Φ CO =24.2 %) at the early stage of photolysis (<5 h). This study demonstrates that the π ‐character modulation on the ancillary bipyridyl ligand is critical for forthcoming catalytic performance. Abstract : In [(C^N)2 Ir III (N^N)] + ‐type complex‐sensitized photolysis, aryl‐substitution—engaging π ‐electron extension from bipyridyl ligand—leads to a positive effect in electron transfer towards the catalytic center, exhibiting 300 % enhancement of the photochemical CO2 to CO conversion activity.